PENINGKATAN EKSISTENSI UMKM MELALUI COMPARATIVE ADVANTAGE DALAM RANGKA MENGHADAPI MEA 2015 DI TEMANGGUNG - Ana Syukriah; Imam Hamdani (Economics Development Analysis Journal, 2013)
Abstrak ___________________________________________________________________ UMKM (Usaha Mikro Kecil dan Menengah) memainkan peran yang sangat penting di dalam pembangunan dan pertumbuhan ekonomi di Indonesia seiring dengan jumlah penduduk yang semakin meningkat. Dengan akan diberlakukanya MEA (Masyarakat Ekonomi ASEAN) pada tahun 2015 akan membawa dampak positif dan dampak negatif kepada UMKM di Indonesia, termasuk juga UMKM yang ada di Temanggung. Dampak positif  yang muncul adalah masyarakat dapat menjual barang-barang hasil produksinya ke Negara di ASEAN dengan mudah, namun dampak negatifnya akan banyak produk-produk yang masuk kedalam negeri sehingga menjadikan persaingan menjadi lebih ketat. Untuk dapat mempertahankan eksistensi UMKM maka dibutuhkan suatu strategi, Salah satunya dengan menggunakan keunggulan komparatif (comparative advantage) yaitu dengan menciptakan produk yang khas dan unik serta memberikan pelayanan yang baik.   Abstract ___________________________________________________________________ This study aims for know the role of women sellers jamu gendong in improving social life, the contribution women make seller of jamu gendong against family income, and the impact the role of women seller of jamu gendong social and economic life family. The data collected consist of primary and secondary data by direct observation, in-depth interviews with selected informants, and documentation. Analysis data using data analysis qualitative with presenting the data in the form of tables be accompanied interpretation so that is obtained a conclusion. The results showed that the social and economic conditions of low family encourage women working in the public sector. Motivation women worked choose jobs sell jamu gendong is capital a little, do not require education / skill high, and solicitation friend or previously already there is brother who worked. Donations the lowest income of women seller of jamu gendong against the overall family income ketegori family is amounted to 20% and donations highest revenue is 72.72%. Impact social life the role of of women sellers jamu gendong is a family afford to send child, whereas impact economic life is increasing the family income which can fulfill needs of family life.